Access to Secondary and Tertiary Education for All Refugees: Steps and Challenges to Overcome - Anselme, Marina L.; Hands, Catriona (Refuge: Canada's Journal on Refugees, 2012)
During situations of displacement, access for refugee youth to secondary educational initiatives is limited at best. However, upon the return of refugees, the national structure of their home country is most often weak and unstable. To ensure the economic, social, and political development of a society that has been severely affected by conflict or disaster, it is imperative that there be a youth population of capable, productive, and educated citizens who may provide an exit strategy from the situation. Future leaders must therefore be given the opportunity to promote the development both of themselves personally, and of their national structures, through learning—notably, secondary, vocational, and tertiary education. This paper underscores the need for and gaps in the provision of secondary educational initiatives, highlighting the many challenges involved in improving refugee youth access to both secondary and vocational education, and highlighting the issues that must be considered by policy and decision makers in order to facilitate and support such access.